Electrokinetic properties of healthy and β-thalassemia erythrocyte membranes under in vitro exposure to static magnetic field - Doltchinkova, Virjinia; Lozanova, Siya; Rukova, Blaga; Nikolov, Rumin; Ivanova, Elitsa; Roumenin, Chavdar (Frontiers in Chemistry, 2023)
The current understanding of the biological impacts of a static magnetic field (SMF) is restricted to the direct interactions of the magnetic field with biological membranes. The electrokinetic (zeta) potential is an electrochemical property of erythrocyte surfaces that is determined by the net electrical charge of molecules exposed at the surface of cell membranes. The surface of the erythrocytes was negatively charged in physiological media after SMF exposure (0.1‒2.0 T). The novel data about electrokinetic parameters of the erythrocytes is determined by microelectrophoresis after SMF-exposure in norm and heterozygous β-thalassemia. The electrokinetic potential of erythrocytes in norm is increased after SMF intensities due to enhanced negatively exposed charges on the outer surface of the membrane accompanied by an increase in light scattering where changes in cell morphology are observed. Conversely, a decrease in the zeta potential of β-thalassemia erythrocytes upon SMF-treatment was determined because of the reduction in the surface electrical charge of the membranes, where a significant decrease in light scattering at 1.5 T and 2.0 T was recorded. Exposure to SMF (0.5–2.0 T) was associated with an increase in the malondialdehyde content in erythrocytes. Biophysical studies regarding the influence of SMF on the electrostatic free energy of cells shows an increase in negative values in healthy erythrocytes, which corresponds to the implementation of a spontaneous process. This is also the process in β-thalassemia cells after SMF exposure with lower negative values of free electrostatic energy than erythrocytes in norm. The electrostatic interaction between the erythrocytes in norm and pathology are involved with the membrane surfaces due to reduction in the extent of FITC-concanavalin A binding to both types of membranes upon SMF exposure. The presented results would have future fundamental applications in biomedicine.